A qualidade de vida da criança durante a internação hospitalar - Pastega, Mariana Gonçalves (2016)
Childhood is characterized by a development process in which the play is essential for the quality of life. Nevertheless, in hospitalization, studies indicate changes in the performance of the play, and consequently, the quality of children's life. It was proposed to assess the child's quality of life during hospitalization. This is a descriptive, cross-sectional research, which proposed to compare two groups, one (Group 1) in the absence of toy room or permanent toy in pediatric ward and the other (Group 2) in the presence of toy or toy room in the pediatric ward. Twelve children were interviewed, 8 belonging to Group 1 and 4 to Group 2, aged six to 12 years, it was used the Autoquestionnaire Qualité De Vie Enfant Imagé (AUQEI), as well as interviews with the participants and their responsible ones. The results revealed in Group 1 the possibility of interaction and play among children, different from Group 2 in which it was noted restrictions on single room (bed-box). As to permanent toy, it was not observed effectiveness regarding access and use on free demand, obtaining satisfactory results in relation to play in the service of occupational therapy. It was found that children who play reported positive feelings (happiness) during the hospitalization experience. In AUQEI scale, it was verified in Group 1 that 37.5% of children have had damages in the quality of life, being the average 49.5 with P.D. = 5.88, above the cutoff of 48 expected to satisfactory quality of life. While in Group 2, the damage was appointed in 75% of the cases, with an average of 46.5 with P.D. = 4.65, that is, below expectations. Statistically, it was not observed significant differences by the Mann-Whitney test (5%) between the comparison of groups, being not rejected the hypothesis that the groups are equal, however, it is considered the particularities and diversities of the groups. The AUQEI instrument showed good psychometric properties when applied to the two groups. The study shows the establishment of a positive relationship to the sense of well being and quality of life for children who play. Moreover, it must be considered the clinical condition, the subjectivity of the way to understand and face this experience and the importance of play, especially as the stimulus. Therefore, it is necessary to expand the look, be careful and sensitive to everything around a hospitalized child, consider that the toy itself often needs incentives to become play, or that even without the toy, playing can be explored and meet the child's whole needs.